Analysis of the Success Factors for Implementing the Independent Curriculum in the Revolutionary Era 4.0 - Wijayanti, Nurulita; Iswan, Iswan; Hadi, Sofian (Universitas Islam Negeri Raden Intan Lampung, 2023)
The aim of the research is to analyze and identify success factors in implementing independent curriculum in the era of revolution 4.0. The research method uses library research with the research object being the success factor in implementing an independent curriculum. The data is collected by documentation, namely looking for data regarding things in the form of articles and journals. Data analysis techniques use the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. The results of this research show that there are eight factors for the success of implementing an independent curriculum in the era of revolution 4.0, namely the existence of structural coordination and communication, local or regional education offices preparing various principles such as the basic framework of the curriculum, madrasah curriculum, developing a curriculum framework, implementing an independent curriculum framework development strategy, providing training to teachers and madrasah heads regarding curriculum implementation, providing continuous instructor support, collecting data online, managing learning resources wisely. It can be concluded that the implementation of an independent curriculum is strongly indicated by technology which makes all parties such as madrasah heads, supervisors, teachers, education staff, the surrounding community and students attend and accompany technological developments.